2017
DOI: 10.1590/1806-9061-2016-0415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sources and Levels of Dietary Zinc on the Performance, Carcass Traits and Blood Parameters of Broilers

Abstract: A total of 400 one-day-old, straight-run, commercial (Ross 308) broiler chicks were used to evaluate the effects of two dietary levels of zinc (Zn) sources on broiler chick performance, carcass traits and blood parameters. Corn-soybean diets were formulated for three rearing phases (starter, grower and finisher). The two dietary treatments applied consisted of the addition per kg of diet of 80mg of inorganic Zn (ZnO) (T1), or 80mg of ZnO plus 42mg of an organic Zn-amino acid complex (Availa-Zn120; Zinpro Corpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 33 publications
9
20
0
Order By: Relevance
“…Likewise, Tayeb and Qader (2012) showed that selenium and vitamin E had no significant effect on carcass weight, carcass parts and dressing percentage at 42 and 49 days of age. As well, our carcass traits findings are consistent with Liu et al (2011), Sarvari et al (2015) and Zakaria et al (2017) who showed that carcass traits were not affected by Zn source or the interaction between Zn source and supplemental Zn level or the high Zn concentration. On contrast, Jahanian et al (2008) reported that increasing Zn supplemental levels from 40 to 80 mg/kg from both inorganic and organic zinc sources increased liver weight percentage.…”
Section: Carcass Traitssupporting
confidence: 91%
“…Likewise, Tayeb and Qader (2012) showed that selenium and vitamin E had no significant effect on carcass weight, carcass parts and dressing percentage at 42 and 49 days of age. As well, our carcass traits findings are consistent with Liu et al (2011), Sarvari et al (2015) and Zakaria et al (2017) who showed that carcass traits were not affected by Zn source or the interaction between Zn source and supplemental Zn level or the high Zn concentration. On contrast, Jahanian et al (2008) reported that increasing Zn supplemental levels from 40 to 80 mg/kg from both inorganic and organic zinc sources increased liver weight percentage.…”
Section: Carcass Traitssupporting
confidence: 91%
“…However, broiler performance was not affected by supplemental Zn levels in the present study. Previous studies had also observed that broiler growth was not affected by dietary Zn concentrations (Bartlett and Smith, 2003; Rossi et al, 2007;Sunder et al, 2008;Owens et al, 2009;Yang et al, 2011;Star et al, 2012;Liao et al, 2013;Pacheco et al, 2017;Zakaria et al, 2017). This is attributed to the Zn content of basal diets (about 30 mg/kg), which is adequate to maintain the growth of broiler chickens from 1 to 42 d of age.…”
Section: Growth Performancementioning
confidence: 80%
“…There was no effect of Zn levels on the tibial ash content of 42-d-old broilers (p>0.05). Research has shown that supplemental Zn increases blood Zn concentration in laying hens and broiler chickens (Tsai et al, 2016;Zakaria et al, 2017). A linear relationship was observed between 0 and 20 mg/kg supplemental Zn and bone Zn content in broiler chickens from 1 to 21 d of age (Ao et al, 2007;Star et al, 2012).…”
Section: Effects Of Dietary Zinc Levels On the Growth Performance Ormentioning
confidence: 95%
“…This may have been due to the fact that zinc promotes protein biosynthesis (Coleman, 1992). Likewise, Zakaria et al (2017) also supplemented broiler feed with organic zinc (Availa ® Zn Zinpro Corporation, Edina, MN, USA). This study showed that feeding broilers with added organic zinc significantly (P ≤ 0.05) improves the level of protein in the blood.…”
Section: Resultsmentioning
confidence: 99%